A kind of anti-ultraviolet card protection film and preparation process
By introducing hydroxyl-containing copolyester and isocyanate modified nanotitanium dioxide into the film substrate of the guard film, and combining polyethylene terephthalate and antioxidant for blending and extrusion, the problem of poor UV resistance of the guard film is solved, and higher UV resistance and heat resistance are achieved.
Patent Information
- Application Number
- CN202410151615.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-02
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-02-02
AI Technical Summary
The existing card protection film has poor UV resistance, which causes the card to turn yellow, age and fade after exposure to the sun outdoors, shortening its service life.
By introducing hydroxyl-containing copolyester into the thin film substrate of the guard film, and using it to form chemical bonds with isocyanate modified nanotitanium dioxide, blending and extruding with polyethylene terephthalate and antioxidant, the ultraviolet resistance of the substrate is improved.
It significantly improves the UV resistance of the card protection film, extends its service life, and enhances the heat resistance of the substrate.
Smart Images

Figure CN118027834B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of card protection films, in particular to an anti-ultraviolet card protection film and a preparation process thereof. Background Art
[0002] In people's daily life and work, they often come into contact with and use various pictures, business cards, various representative certificates, identity cards, work certificates, and other certificates and credit cards. Due to long-term contact and use, these certificates and cards are very easy to be contaminated and damaged, which adds some unnecessary troubles to people; card protection film is a composite film used for plastic bonding of various certificates and cards, which has the advantages of anti-pollution, oil and water resistance, anti-deformation, anti-damage, and anti-alteration, and has attracted more and more attention from people from all walks of life; however, since some cards are frequently used and often exposed to the sun outdoors, the cards turn yellow, age and fade, resulting in the loss of key information and greatly shortening the service life of the cards. Therefore, a card protection film substrate with strong UV resistance has been developed, which has become a hot topic of current research to broaden its application field and meet people's growing needs in life and work.
[0003] The base film of the card protection film is generally a polyethylene terephthalate film, which has good transparency, good tear strength, acid resistance, alkali resistance, oil resistance, and resistance to various organic solvents, but poor UV resistance. For example, after a color photo or picture is protected by a card protection film, it will gradually fade when hung in a sunny room. Color slides will also fade significantly after continuous exposure under a standard projection light source. Similar problems are also encountered in the preservation and display of some cultural relics. The main reason for these problems is ultraviolet radiation. The damage of ubiquitous ultraviolet rays to important certificates and documents cannot be ignored. However, there is currently little research on anti-ultraviolet card protection films, and the prepared card protection films have weak UV resistance and poor heat resistance, which limits the further application of the card protection films and reduces the service life of the card protection films.
[0004] The present invention modifies the film substrate of the card protection film, introduces hydroxyl-containing copolyester, utilizes the hydroxyl groups on its surface to chemically bond with the isocyanate groups of isocyanate-modified nano titanium dioxide, and then introduces titanium dioxide with excellent anti-ultraviolet performance into the substrate through co-extrusion with polyethylene terephthalate and an antioxidant, thereby improving the compatibility with the substrate, so that the prepared card protection film substrate has good anti-ultraviolet performance, thereby improving the anti-ultraviolet ability of the card protection film. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art, provide an anti-ultraviolet card protection film and a preparation process, and solve the problem of poor anti-ultraviolet performance of the existing card protection film.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A preparation process of an anti-ultraviolet card protection film, wherein the structure of the card protection film is ethylene-vinyl acetate copolymer binder, polyethylene and modified polyethylene terephthalate substrate from the inner layer to the outer layer, and the preparation process is carried out according to the following steps:
[0008] (1) The dried polyethylene terephthalate, titanium dioxide grafted copolyester and antioxidant are mixed and stirred uniformly in a high-speed mixer, and then melted on a twin-screw extruder. The temperature of each section of the barrel is 280-320° C., and the extruder is extruded at a screw speed of 60-100 r / min, and the pellets are water-cooled to obtain a modified polyethylene terephthalate substrate.
[0009] (2) After the modified polyethylene terephthalate substrate is melted, it is biaxially stretched at 80-90°C to obtain a polyester film layer, which is then subjected to corona treatment with a corona machine. Then, the polyethylene is melted at 180-220°C, and a polyethylene film is cast by a casting machine and coated on the polyester film layer. Then, the ethylene-vinyl acetate copolymer is melted at 175-210°C, and an ethylene-vinyl acetate film is cast by a casting machine and coated on the polyethylene film layer. The film is cooled, rolled, and wound by an extruder roller to obtain an anti-ultraviolet card film.
[0010] Preferably, in step (1), the ratio of polyethylene terephthalate, titanium dioxide grafted copolyester and antioxidant is 100g:0.1-2g:0.3-0.8g.
[0011] Preferably, in step (2), the extruder speed is 30-60 r / min, and the pulling speed is 5-10 m / s.
[0012] Preferably, the preparation process of the titanium dioxide grafted copolyester is carried out according to the following steps:
[0013] S1. Under a nitrogen atmosphere, 3-boric acid-5-methoxybenzoic acid and toluene solvent were added to a reaction bottle equipped with a condenser. After stirring evenly, 3-bromo-5-methoxybenzoic acid, tetrakis(triphenylphosphine)palladium, sodium carbonate and deionized water were added, and the reaction was stirred. After the reaction was completed, ethyl acetate and deionized water were extracted, and the organic phase was purified by column chromatography. After drying, the structural formula was obtained. of dimethoxybiphenyl dicarboxylic acid.
[0014] S2. Under a nitrogen atmosphere, add terephthalic acid, dimethoxybiphenyl dicarboxylic acid, ethylene glycol and catalyst tetrabutyl titanate to a reaction bottle equipped with a condenser, stir at 210-240°C until the system is uniform and transparent, heat to 245-270°C for polycondensation reaction for 2-6 hours, cool the material, add the product to glacial acetic acid and hydrobromic acid aqueous solution, heat to 105-130°C, condense and reflux for 5-10 hours, after the reaction is completed, cool and filter, extract with methyl tert-butyl ether, purify by organic phase column chromatography, and dry to obtain hydroxyl-containing copolyester.
[0015] S3. Add isocyanate-modified nano titanium dioxide, hydroxyl-containing copolyester and N,N-dimethylformamide into a reaction flask, react at 80-100° C. for 4-10 hours, cool and filter to obtain titanium dioxide grafted copolyester.
[0016] Preferably, in step S1, the ratio of 3-boric acid-5-methoxybenzoic acid, 3-bromo-5-methoxybenzoic acid, tetrakis(triphenylphosphine)palladium, and sodium carbonate is 1 mol: 1.05-1.2 mol: 0.02-0.04 mol: 2.5-3.5 mol.
[0017] Preferably, in step S1, the reaction temperature is 100-120° C., and the reaction time is 4-8 h.
[0018] Preferably, in step S2, the ratio of terephthalic acid, dimethoxybiphenyl dicarboxylic acid, ethylene glycol and tetrabutyl titanate is 0.9-0.95 mol: 0.05-0.1 mol: 1.5-1.8 mol: 0.001-0.003 mol.
[0019] Preferably, the mass fraction of the hydrobromic acid aqueous solution in step S2 is 40-48%.
[0020] Preferably, in step S3, the ratio of isocyanate-modified nano titanium dioxide to hydroxyl-containing copolyester is 1 g:2-15 g.
[0021] By adopting the above technical solution, the beneficial effects of the present invention are:
[0022] The invention uses 3-boric acid-5-methoxybenzoic acid and 3-bromo-5-methoxybenzoic acid to undergo coupling reaction under the action of tetrakis(triphenylphosphine)palladium and sodium carbonate to obtain dimethoxybiphenyl dicarboxylic acid, then reacts with terephthalic acid and ethylene glycol under the catalysis of tetrabutyl titanate to undergo polycondensation reaction, and then removes the methoxy group through the action of glacial acetic acid and hydrobromic acid to obtain hydroxyl-containing copolyester; utilizes the hydroxyl group of the hydroxyl-containing copolyester to generate bonding with the isocyanate group of isocyanate-modified nano titanium dioxide to obtain titanium dioxide grafted copolyester, then mixes and extrudes with polyethylene terephthalate and an antioxidant to obtain a modified polyethylene terephthalate substrate, performs surface corona treatment on the substrate, and sequentially coats polyethylene and ethylene-vinyl acetate copolymer binder on the substrate to obtain an anti-ultraviolet card protection film.
[0023] Nano titanium dioxide acts as a UV shielding agent, which shields UV light by absorbing and scattering it. It has a small particle size, contains a relatively large number of effective UV-resistant particles, and has a low UV transmittance, so it can effectively reflect and absorb UV light. After the nano titanium dioxide in the card protection film substrate is modified with isocyanate, the isocyanate groups on its surface can produce chemical bonding with the hydroxyl groups of the hydroxyl-containing copolyester with strong binding force, forming a molecular film on the surface of titanium dioxide to hinder the mutual contact between particles, making it difficult for highly active nanoparticles to agglomerate, improving the interfacial compatibility between nano titanium dioxide and the substrate, and reducing the agglomeration of nanoparticles, thereby better absorbing and reflecting ultraviolet light in the medium and long wave regions, further improving the anti-ultraviolet performance of the card protection film.
[0024] The modified polyethylene terephthalate contains units with a similar structure to the card protection film substrate, which improves the dispersibility of nano-titanium dioxide in the polymer matrix, makes it evenly distributed in the substrate, and weakens the damage of ultraviolet light to the polyethylene terephthalate molecules; at the same time, the biphenyl aromatic structure it contains increases the rigidity of the molecular chain, increases the intramolecular steric hindrance and reduces the mobility of the chain links, thereby helping to improve the heat resistance of polyester, which is manifested as an improvement in the substrate's anti-ultraviolet performance, thereby extending the service life of the card protection film. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Schematic diagram of the structure of the UV-resistant card protection film. DETAILED DESCRIPTION
[0026] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0027] 3-Boric acid-5-methoxybenzoic acid, CAS number is 1050424-08-2.
[0028] 3-Bromo-5-methoxybenzoic acid, CAS number is 157893-14-6.
[0029] Preparation of isocyanate-modified nano titanium dioxide: Add 2 g of nano titanium dioxide and 400 mL of toluene solvent into a reaction flask, stir evenly, add 0.6 mL of toluene diisocyanate, reflux at 120°C for 2 h, cool and filter, wash the filter cake with toluene, and dry to obtain isocyanate-modified nano titanium dioxide.
[0030] Example 1
[0031] (1) Under nitrogen atmosphere, add 10 mmol of 3-boric acid-5-methoxybenzoic acid and 200 mL of toluene solvent to a reaction bottle equipped with a condenser, stir evenly, add 11 mmol of 3-bromo-5-methoxybenzoic acid, 0.3 mmol of tetrakis(triphenylphosphine)palladium, 30 mmol of sodium carbonate and 40 mL of deionized water, react at 110° C. for 6 h, extract with ethyl acetate and deionized water, purify the organic phase by column chromatography, and dry to obtain dimethoxybiphenyl dicarboxylic acid. The preparation process is as follows:
[0032]
[0033] (2) Under nitrogen atmosphere, add 0.92mmol terephthalic acid, 0.08mmol dimethoxybiphenyl dicarboxylic acid, 1.6mmol ethylene glycol and 0.0025mmol catalyst tetrabutyl titanate to a reaction bottle equipped with a condenser, stir at 225°C until the system is homogeneous and transparent, heat to 260°C for polycondensation reaction for 5h, cool and discharge, add the product to 30mL glacial acetic acid and 90mL 45% hydrobromic acid aqueous solution, heat to 120°C, condense and reflux for 8h, after the reaction is completed, cool and filter, extract with methyl tert-butyl ether, purify the organic phase by column chromatography, and dry to obtain hydroxyl-containing copolyester. The preparation process principle is as follows:
[0034]
[0035] (3) Add 5 g of isocyanate-modified nano-titanium dioxide, 50 g of hydroxyl-containing copolyester and 200 mL of N,N-dimethylformamide into a reaction flask, react at 95° C. for 8 h, cool and filter to obtain titanium dioxide grafted copolyester.
[0036] (4) 100 g of dried polyethylene terephthalate, 0.1 g of titanium dioxide grafted copolyester and 0.3 g of antioxidant 1010 were mixed and stirred evenly in a high-speed mixer, and then melted on a twin-screw extruder. The temperature of each section of the barrel was 300° C. The extruder was extruded at a screw speed of 80 r / min, and the pellets were water-cooled to obtain a modified polyethylene terephthalate substrate.
[0037] (5) After the modified polyethylene terephthalate substrate is melted, it is biaxially stretched at 85°C to obtain a polyester film layer, which is then treated with a corona machine. Then, the polyethylene is melted at 200°C, and a polyethylene film is cast by a casting machine and coated on the polyester film layer. Then, the ethylene-vinyl acetate copolymer is melted at 205°C, and an ethylene-vinyl acetate film is cast by a casting machine and coated on the polyethylene film layer. The film is cooled, rolled, and wound by an extruder roller with a rotation speed of 45 r / min and a pulling speed of 8 m / s to obtain an anti-ultraviolet card film.
[0038] Example 2
[0039] (1) Under nitrogen atmosphere, 2 mmol of 3-boric acid-5-methoxybenzoic acid and 30 mL of toluene solvent were added to a reaction bottle equipped with a condenser. After stirring, 2.1 mmol of 3-bromo-5-methoxybenzoic acid, 0.04 mmol of tetrakis(triphenylphosphine)palladium, 5 mmol of sodium carbonate and 6 mL of deionized water were added. After reacting at 120° C. for 4 h, the mixture was extracted with ethyl acetate and deionized water, and the organic phase was purified by column chromatography and dried to obtain dimethoxybiphenyldicarboxylic acid.
[0040] (2) Under nitrogen atmosphere, 0.9 mmol of terephthalic acid, 0.1 mmol of dimethoxybiphenyl dicarboxylic acid, 1.5 mmol of ethylene glycol and 0.001 mmol of catalyst tetrabutyl titanate were added to a reaction bottle equipped with a condenser, and the mixture was stirred at 240° C. until the system was homogeneous and transparent, and the temperature was raised to 270° C. for polycondensation reaction for 2 h. The product was cooled and discharged, and the product was added to 30 mL of glacial acetic acid and 85 mL of a 48% hydrobromic acid aqueous solution, and the temperature was raised to 130° C. and condensed and refluxed for reaction for 5 h. After the reaction was completed, the mixture was cooled and filtered, extracted with methyl tert-butyl ether, purified by organic phase column chromatography, and dried to obtain a hydroxyl-containing copolyester.
[0041] (3) Add 5 g of isocyanate-modified nano-titanium dioxide, 10 g of hydroxyl-containing copolyester and 250 mL of N,N-dimethylformamide into a reaction flask, react at 100° C. for 4 h, cool and filter to obtain titanium dioxide grafted copolyester.
[0042] (4) 100 g of dried polyethylene terephthalate, 0.7 g of titanium dioxide grafted copolyester and 0.35 g of antioxidant 1010 were mixed and stirred uniformly in a high-speed mixer, and then melted on a twin-screw extruder. The temperature of each section of the barrel was 280° C. The extruder was extruded at a screw speed of 100 r / min, and the pellets were water-cooled to obtain a modified polyethylene terephthalate substrate.
[0043] (5) After the modified polyethylene terephthalate substrate is melted, it is biaxially stretched at 90°C to obtain a polyester film layer, which is then treated with a corona machine. Then, the polyethylene is melted at 220°C, and a polyethylene film is cast by a casting machine and coated on the polyester film layer. Then, the ethylene-vinyl acetate copolymer is melted at 210°C, and an ethylene-vinyl acetate film is cast by a casting machine and coated on the polyethylene film layer. The film is cooled, rolled, and wound by an extruder roller with a rotation speed of 30 r / min and a pulling speed of 5 m / s to obtain an anti-ultraviolet card film.
[0044] Example 3
[0045] (1) Under a nitrogen atmosphere, 25 mmol of 3-boric acid-5-methoxybenzoic acid and 625 mL of toluene solvent were added to a reaction bottle equipped with a condenser. After stirring, 30 mmol of 3-bromo-5-methoxybenzoic acid, 1 mmol of tetrakis(triphenylphosphine)palladium, 87.5 mmol of sodium carbonate and 125 mL of deionized water were added. After reacting at 100° C. for 8 h, the mixture was extracted with ethyl acetate and deionized water, and the organic phase was purified by column chromatography and dried to obtain dimethoxybiphenyldicarboxylic acid.
[0046] (2) Under nitrogen atmosphere, 0.95 mmol of terephthalic acid, 0.05 mmol of dimethoxybiphenyl dicarboxylic acid, 1.8 mmol of ethylene glycol and 0.003 mmol of tetrabutyl titanate catalyst were added to a reaction bottle equipped with a condenser, and the mixture was stirred at 210° C. until the system was homogeneous and transparent, and the mixture was heated to 245° C. for polycondensation reaction for 6 h. The product was cooled and discharged, and the product was added to 35 mL of glacial acetic acid and 100 mL of a 40% by mass aqueous solution of hydrobromic acid, and the mixture was heated to 105° C. and condensed and refluxed for reaction for 10 h. After the reaction was completed, the mixture was cooled and filtered, extracted with methyl tert-butyl ether, purified by organic phase column chromatography, and dried to obtain a hydroxyl-containing copolyester.
[0047] (3) Add 5 g of isocyanate-modified nano-titanium dioxide, 75 g of hydroxyl-containing copolyester and 150 mL of N,N-dimethylformamide into a reaction flask, react at 80° C. for 10 h, cool and filter to obtain titanium dioxide grafted copolyester.
[0048] (4) 100 g of dried polyethylene terephthalate, 1.4 g of titanium dioxide grafted copolyester and 0.6 g of antioxidant 1010 were mixed and stirred uniformly in a high-speed mixer, and then melted on a twin-screw extruder. The temperature of each section of the barrel was 320° C. The extruder was extruded at a screw speed of 60 r / min, and the pellets were water-cooled to obtain a modified polyethylene terephthalate substrate.
[0049] (5) After the modified polyethylene terephthalate substrate is melted, it is biaxially stretched at 80°C to obtain a polyester film layer, which is then treated with a corona machine. Then, the polyethylene is melted at 180°C, and a polyethylene film is cast by a casting machine and coated on the polyester film layer. Then, the ethylene-vinyl acetate copolymer is melted at 175°C, and an ethylene-vinyl acetate film is cast by a casting machine and coated on the polyethylene film layer. The film is cooled, rolled, and wound by an extruder roller with a rotation speed of 60 r / min and a pulling speed of 10 m / s to obtain an anti-ultraviolet card film.
[0050] Example 4
[0051] (1) Under nitrogen atmosphere, 8 mmol of 3-boric acid-5-methoxybenzoic acid and 176 mL of toluene solvent were added to a reaction bottle equipped with a condenser. After stirring, 9.2 mmol of 3-bromo-5-methoxybenzoic acid, 0.28 mmol of tetrakis(triphenylphosphine)palladium, 25.6 mmol of sodium carbonate and 36 mL of deionized water were added. After reacting at 105° C. for 7 h, the mixture was extracted with ethyl acetate and deionized water, and the organic phase was purified by column chromatography and dried to obtain dimethoxybiphenyldicarboxylic acid.
[0052] (2) Under nitrogen atmosphere, 0.91 mmol of terephthalic acid, 0.09 mmol of dimethoxybiphenyl dicarboxylic acid, 1.7 mmol of ethylene glycol and 0.0015 mmol of tetrabutyl titanate catalyst were added to a reaction bottle equipped with a condenser, and the mixture was stirred at 230° C. until the system was homogeneous and transparent, and the temperature was raised to 265° C. for polycondensation reaction for 5 h. The product was cooled and discharged, and the product was added to 32 mL of glacial acetic acid and 95 mL of a 45% by mass hydrobromic acid aqueous solution, and the temperature was raised to 125° C. and condensed and refluxed for reaction for 9 h. After the reaction was completed, the mixture was cooled and filtered, extracted with methyl tert-butyl ether, purified by organic phase column chromatography, and dried to obtain a hydroxyl-containing copolyester.
[0053] (3) Add 5 g of isocyanate-modified nano-titanium dioxide, 45 g of hydroxyl-containing copolyester and 225 mL of N,N-dimethylformamide into a reaction flask, react at 95° C. for 8 h, cool and filter to obtain titanium dioxide grafted copolyester.
[0054] (4) 100 g of dried polyethylene terephthalate, 2 g of titanium dioxide grafted copolyester and 0.8 g of antioxidant 1010 were mixed and stirred uniformly in a high-speed mixer, and then melted on a twin-screw extruder. The temperature of each section of the barrel was 310° C. The extruder was extruded at a screw speed of 90 r / min, and the pellets were water-cooled to obtain a modified polyethylene terephthalate substrate.
[0055] (5) After the modified polyethylene terephthalate substrate is melted, it is biaxially stretched at 80°C to obtain a polyester film layer, which is then treated with a corona machine. Then, the polyethylene is melted at 210°C, and a polyethylene film is cast by a casting machine and coated on the polyester film layer. Then, the ethylene-vinyl acetate copolymer is melted at 190°C, and an ethylene-vinyl acetate film is cast by a casting machine and coated on the polyethylene film layer. The film is cooled, rolled, and wound by an extruder roller with a rotation speed of 50 r / min and a pulling speed of 8 m / s to obtain an anti-ultraviolet card film.
[0056] Comparative Example 1
[0057] (1) 100 g of dried polyethylene terephthalate, 0.1 g of hydroxyl-containing copolyester (prepared in Example 1) and 0.3 g of antioxidant 1010 were mixed and stirred uniformly in a high-speed mixer, and then melted on a twin-screw extruder. The temperature of each section of the barrel was 300° C., and the mixture was extruded at a screw speed of 80 r / min, and pelletized by water cooling to obtain a modified polyethylene terephthalate substrate.
[0058] (2) After the modified polyethylene terephthalate substrate is melted, it is biaxially stretched at 85°C to obtain a polyester film layer, which is then subjected to corona treatment by a corona machine. Then, the polyethylene is melted at 200°C, and a polyethylene film is cast by a casting machine and coated on the polyester film layer. Then, the ethylene-vinyl acetate copolymer is melted at 205°C, and an ethylene-vinyl acetate film is cast by a casting machine and coated on the polyethylene film layer. The film is then cooled, rolled, and wound by an extruder roller with a rotation speed of 45 r / min and a pulling speed of 8 m / s to obtain a card protection film.
[0059] Comparative Example 2
[0060] (1) Add 5 g of titanium dioxide, 50 g of hydroxyl-containing copolyester (prepared in Example 1) and 200 mL of N,N-dimethylformamide into a reaction flask, blend at 95° C. for 8 h, cool and filter to obtain a titanium dioxide and copolyester blend.
[0061] (2) 100 g of dried polyethylene terephthalate, 0.1 g of nano-titanium dioxide and copolyester blend, and 0.3 g of antioxidant 1010 were mixed and stirred uniformly in a high-speed mixer, and then melted on a twin-screw extruder. The temperature of each section of the barrel was 300° C. The mixture was extruded at a screw speed of 80 r / min, and pelletized by water cooling to obtain a modified polyethylene terephthalate substrate.
[0062] (3) After the modified polyethylene terephthalate substrate is melted, it is biaxially stretched at 85°C to obtain a polyester film layer, which is then subjected to corona treatment by a corona machine. Then, the polyethylene is melted at 200°C, and a polyethylene film is cast by a casting machine and coated on the polyester film layer. Then, the ethylene-vinyl acetate copolymer is melted at 205°C, and an ethylene-vinyl acetate film is cast by a casting machine and coated on the polyethylene film layer. The film is then cooled, rolled, and wound by an extruder roller with a rotation speed of 45 r / min and a pulling speed of 8 m / s to obtain a card protection film.
[0063] Comparative Example 3
[0064] (1) 100 g of dried polyethylene terephthalate, 0.1 g of isocyanate-modified nano-titanium dioxide and 0.3 g of antioxidant 1010 were mixed and stirred uniformly in a high-speed mixer, and then melted on a twin-screw extruder. The temperature of each section of the barrel was 300° C., and the mixture was extruded at a screw speed of 80 r / min, and pelletized by water cooling to obtain a modified polyethylene terephthalate substrate.
[0065] (2) After the modified polyethylene terephthalate substrate is melted, it is biaxially stretched at 85°C to obtain a polyester film layer, which is then subjected to corona treatment by a corona machine. Then, the polyethylene is melted at 200°C, and a polyethylene film is cast by a casting machine and coated on the polyester film layer. Then, the ethylene-vinyl acetate copolymer is melted at 205°C, and an ethylene-vinyl acetate film is cast by a casting machine and coated on the polyethylene film layer. The film is then cooled, rolled, and wound by an extruder roller with a rotation speed of 45 r / min and a pulling speed of 8 m / s to obtain a card protection film.
[0066] Anti-ultraviolet performance test: The UV transmittance of the prepared card protection film at wavelengths of 340nm, 360nm and 400nm was tested using a UV-visible spectrophotometer.
[0067] Table 1 Anti-ultraviolet performance test
[0068]
[0069] Generally speaking, the lower the UV transmittance, the better the UV resistance of the material; it can be seen from the test results in the above table that with the increase of the titanium dioxide content in the card protection film, the UV transmittance at different wavelengths is significantly reduced. The UV transmittance of the card protection film in Example 4 at different wavelengths is less than 10%, and it has excellent UV resistance. This is because nano titanium dioxide, as a UV shielding agent, has the characteristics of low UV transmittance and can effectively reflect and absorb ultraviolet rays; after the nano titanium dioxide in the card protection film substrate is modified with isocyanate, the isocyanate groups on its surface can produce chemical bonding with the hydroxyl groups of the hydroxyl-containing copolyester, forming a molecular film on the surface of titanium dioxide to hinder the mutual contact between particles. , making it difficult for highly active nanoparticles to agglomerate, improving the interfacial compatibility between nano-titanium dioxide and the substrate, and reducing the agglomeration of nanoparticles; at the same time, due to the small particle size of nano-titanium dioxide, the modified polyethylene terephthalate contains units with a structure similar to that of the card protection film substrate, which improves the dispersibility of nano-titanium dioxide in the polymer matrix and makes it evenly distributed in the substrate, thereby better absorbing ultraviolet light in the medium and long wave regions; the titanium dioxide particles are well dispersed and small in size, and contain a relatively large number of effective anti-ultraviolet particles, which absorb and scatter ultraviolet light to shield the ultraviolet light, weaken the damage of ultraviolet light to polyethylene terephthalate molecules, and thus improve the anti-ultraviolet performance of the card protection film.
[0070] Comparative Example 1 does not contain nano titanium dioxide particles and has no anti-ultraviolet ability, so the ultraviolet transmittance is relatively high; the nano titanium dioxide in Comparative Example 2 is not modified and does not produce chemical reaction with the polyethylene terephthalate substrate, resulting in poor interface compatibility between the two, making the particles unevenly dispersed, and thus resulting in poor anti-ultraviolet performance of the card protection film; in Comparative Example 3, the nano titanium dioxide is modified with isocyanate, and the ultraviolet transmittance is low, but not as good as that of the embodiment.
[0071] Thermal stability performance test: The thermal stability of the sample was analyzed using a TG thermogravimetric analyzer with a heating rate of 10°C / min, a temperature range of 25-600°C, and a nitrogen flow rate of 30mL / min.
[0072] The prepared modified polyethylene terephthalate substrate was placed in an ultraviolet accelerated aging machine, irradiated with a 220W mercury light source for 480 hours, and then the glass transition temperature test and thermal decomposition temperature test were performed.
[0073]
[0074]
[0075] It can be seen from the test data in the above table that after 480 hours of irradiation with an ultraviolet accelerated aging machine, the glass transition temperature and the thermal decomposition temperature of the modified polyethylene terephthalate substrate at a weight loss of 10% in the embodiment have no obvious changes compared with those before ultraviolet irradiation, indicating that the prepared modified polyethylene terephthalate has a certain anti-ultraviolet ability, thereby improving the anti-ultraviolet performance of the card protection film; this is because after the titanium dioxide grafted copolyester is added to the modified polyethylene terephthalate, titanium dioxide can inhibit the damage of ultraviolet light to the polymer material. At the same time, the modified polyethylene terephthalate contains structural units similar to the structure of the substrate, and has good interface compatibility, so that titanium dioxide is evenly dispersed. At the same time, the biphenyl aromatic structure contained in it increases the rigidity of the molecular chain, increases the intramolecular steric hindrance and reduces the activity of the chain links, thereby helping to improve the heat resistance of the polyester, which is further manifested as the improvement of the anti-ultraviolet performance of the card protection film.
[0076] No nano-titanium dioxide was added to Comparative Example 1, and it had no UV resistance. After being irradiated by an ultraviolet accelerated aging machine for 480 hours, its glass transition temperature and thermal decomposition temperature of 10% weight loss decreased significantly, and its UV resistance was poor. The nano-titanium dioxide in Comparative Example 2 was not modified, and its compatibility with copolyester was poor. Its dispersibility in the polyethylene terephthalate substrate was not good, and the UV resistance of the card film material was lower than that of the embodiments.
[0077] In Comparative Example 3, after being modified with isocyanate, the nano-titanium dioxide has better compatibility with the copolyester and better dispersibility in the polyethylene terephthalate substrate. The decrease in its glass transition temperature and 10% weight loss thermal decomposition temperature is smaller, but the decrease is higher than that in the embodiments.
[0078] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A preparation process of an anti-ultraviolet card protection film, characterized in that the structure of the card protection film is ethylene-vinyl acetate copolymer binder, polyethylene and modified polyethylene terephthalate substrate from inner layer to outer layer, and the preparation process is carried out according to the following steps: (1) Mixing and stirring the dried polyethylene terephthalate, titanium dioxide grafted copolyester and antioxidant in a high-speed mixer, and then melting them on a twin-screw extruder. The temperature of each section of the barrel is 280-320° C., extruding at a screw speed of 60-100 r / min, and water-cooling and pelletizing to obtain a modified polyethylene terephthalate substrate; (2) After the modified polyethylene terephthalate substrate is melted, it is biaxially stretched at 80-90°C to obtain a polyester film layer, which is subjected to corona treatment by a corona machine. Then, polyethylene is melted at 180-220°C, and a polyethylene film is cast by a casting machine and coated on the polyester film layer. Then, ethylene-vinyl acetate copolymer is melted at 175-210°C, and an ethylene-vinyl acetate film is cast by a casting machine and coated on the polyethylene film layer. The film is cooled and rolled by an extruder roller, and then wound and rolled to obtain an anti-ultraviolet card film. The preparation process of the titanium dioxide grafted copolyester is carried out according to the following steps: S1. In a nitrogen atmosphere, 3-boric acid-5-methoxybenzoic acid and toluene solvent were added to a reaction bottle equipped with a condenser. After stirring evenly, 3-bromo-5-methoxybenzoic acid, tetrakis(triphenylphosphine)palladium, sodium carbonate and deionized water were added, and the reaction was stirred. After the reaction was completed, ethyl acetate and deionized water were extracted, and the organic phase was purified by column chromatography. After drying, the structural formula was obtained. Dimethoxybiphenyl dicarboxylic acid; S2. Under a nitrogen atmosphere, add terephthalic acid, dimethoxybiphenyl dicarboxylic acid, ethylene glycol and catalyst tetrabutyl titanate to a reaction bottle equipped with a condenser, stir at 210-240° C. until the system is homogeneous and transparent, heat to 245-270° C. for polycondensation reaction for 2-6 hours, cool the material, add the product to glacial acetic acid and hydrobromic acid aqueous solution, heat to 105-130° C., condense and reflux for reaction for 5-10 hours, and after the reaction is completed, cool and filter, extract with methyl tert-butyl ether, purify the organic phase by column chromatography, and dry to obtain a hydroxyl-containing copolyester; S3, adding isocyanate-modified nano titanium dioxide, hydroxyl-containing copolyester and N,N-dimethylformamide into a reaction flask, reacting at 80-100° C. for 4-10 hours, cooling and filtering to obtain titanium dioxide grafted copolyester; In the step (1), the ratio of polyethylene terephthalate, titanium dioxide grafted copolyester and antioxidant is 100g: 0.1-2g: 0.3-0.8g; In step S1, the ratio of 3-boric acid-5-methoxybenzoic acid, 3-bromo-5-methoxybenzoic acid, tetrakis(triphenylphosphine)palladium, and sodium carbonate is 1 mol: 1.05-1.2mol:0.02-0.04mol:2.5-3.5mol; In the step S2, the ratio of terephthalic acid, dimethoxybiphenyl dicarboxylic acid, ethylene glycol, and tetrabutyl titanate is 0.9-0.95 mol: 0.05-0.1 mol: 1.5-1.8 mol: 0.001-0.003 mol; In the step S3, the ratio of isocyanate-modified nano titanium dioxide to hydroxyl-containing copolyester is 1 g:2-15 g.
2. The process for preparing the UV-resistant card protection film according to claim 1, characterized in that: In the step (2), the extruder speed is 30-60 r / min, and the pulling speed is 5-10 m / s.
3. The process for preparing the UV-resistant card film according to claim 1, characterized in that: In step S1, the reaction temperature is 100-120° C. and the reaction time is 4-8 hours.
4. The process for preparing the UV-resistant card protection film according to claim 1, characterized in that: The mass fraction of the hydrobromic acid aqueous solution in step S2 is 40-48%.
Citation Information
Patent Citations
High-quality card protection membrane and preparation method thereof
CN108394160A
Cited By
Breakage-proof foam protective film for packaging and transportation and preparation method of breakage-proof foam protective film
CN120986025A
A rupture-resistant foam protective film for packaging and transportation and its preparation method
CN120986025B